2007
DOI: 10.1186/1471-2458-7-92
|View full text |Cite
|
Sign up to set email alerts
|

Designing and conducting tabletop exercises to assess public health preparedness for manmade and naturally occurring biological threats

Abstract: Background: Since 2001, state and local health departments in the United States (US) have accelerated efforts to prepare for high-impact public health emergencies. One component of these activities has been the development and conduct of exercise programs to assess capabilities, train staff and build relationships. This paper summarizes lessons learned from tabletop exercises about public health emergency preparedness and about the process of developing, conducting, and evaluating them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
78
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 18 publications
5
78
0
1
Order By: Relevance
“…There is considerable variability in how exercises are designed and conducted as well as a need for a stronger evidence base on best practices. 1 This article shows how a local public health agency and its community partners evolved in the planning, use, and evaluation of a series of exercises for pandemic influenza preparedness.…”
mentioning
confidence: 99%
“…There is considerable variability in how exercises are designed and conducted as well as a need for a stronger evidence base on best practices. 1 This article shows how a local public health agency and its community partners evolved in the planning, use, and evaluation of a series of exercises for pandemic influenza preparedness.…”
mentioning
confidence: 99%
“…In addition, exercises can be used to evaluate the performance of individuals, specific agencies, or an overall (multi-agency) system. 4,5 However, the majority of exercises held by public health agencies are not evaluative in nature, but rather intended for purposes of training [6][7][8][9][10] or relationship building. 11 For instance, in the 2008 National Profile, 76% of the LHDs that participated in exercises reported that they revised their written emergency-response plans based on recommendations from an exercise after-action report (AAR).…”
mentioning
confidence: 99%
“…A tabletop design involves an evolving hypothetical scenario of a disease outbreak or disaster, with facilitated group discussions and some level of collective decision making by participants. The unfolding scenario exercises the internal communication and coordination among disciplines within health departments or organizations, as well as the communication and coordination with partner agencies, such as health care facilities and emergency medical service agencies (Dausey, Buehler, & Lurie, 2007).…”
mentioning
confidence: 99%